Implementation of Green Ergonomics to Improve Work Environment Conditions by Using the Sustainable Work Index (SWI) in the Shoe Manufacturing Industry - Sukapto, Paulus; Geovando Gita, Graemmy; Amanda, Gabriela; Liauw, Justin; Gunawan, Maisie (Ann Publisher, 2025)
Background. The work system consists of people, equipment, and environments that are robustly integrated to achieve the goals of the work system. Aims. The purpose of this study is to evaluate and improve the conditions of the work environment with a Green Ergonomics approach using the Ergonomic Triad Model that focuses on the Sustainable Work Index (SWI). Method. The four SWI factors that were analyzed were Human Work Factor (HWF), Workstation Design Factor (WDF), Organizational Environment Factor (OEF), and Environmental Conditions Factor (ECF). Result. The results of the initial SWI calculation were in the Materials Inspection (68.45%) and Packing (63.83%) departments, categorized as